Effects of Ferroptosis on the Metabolome in Cardiac Cells: The Role of Glutaminolysis - Keishla M. Rodríguez-Graciani; Xavier R. Chapa-Dubocq; Esteban J. Ayala-Arroyo; Ivana Chaves-Negrón; Sehwan Jang; Nataliya Chorna; Taber S. Maskrey; Peter Wipf; Sabzali Javadov (MDPI AG, 2022)
Ferroptosis is a novel iron-dependent regulated cell death mechanism that affects cell metabolism; however, a detailed metabolomic analysis of ferroptotic cells is not yet available. Here, we elucidated the metabolome of H9c2 cardioblasts by gas chromatography-mass spectrometry during ferroptosis induced by RSL3, a GPX4 inhibitor, in the presence of ferrostatin-1 (a ferroptosis inhibitor), XJB-5-131 (a mitochondrial-targeted ROS scavenger), or TSM-1005-44 (a newly developed cellular ROS scavenger). Results demonstrated that RSL3 decreased the levels of amino acids involved in glutathione synthesis more than two-fold. In contrast, saturated fatty acids levels were markedly increased in RSL3-challenged cells, with no effects on unsaturated fatty acids. RSL3 significantly altered the levels of mitochondrial tricarboxylic acid cycle intermediates; isocitrate and 2-oxoglutarate were found to increase, whereas succinate was significantly decreased in RSL3-challenged cells. Ferrostatin-1, XJB-5-131, and TSM-1005-44 prevented RSL3-induced cell death and conserved the metabolomic profile of the cells. Since 2-oxoglutarate is involved in the regulation of ferroptosis, particularly through glutamine metabolism, we further assessed the role of glutaminolysis in ferroptosis in H9c2 cardioblasts. Genetic silencing of GLS1, which encodes the K-type mitochondrial glutaminase (glutaminase C), protected against ferroptosis in the early stage. In conclusion, our study demonstrates that RSL3-induced ferroptosis impairs the metabolome of H9c2 cardioblasts.